Water absorption, mechanical, and thermal properties of halloysite nanotube reinforced vinyl-ester nanocomposites - Alhuthali, A.; Low, It Meng (Springer, 2013)
Halloysite nanotube (HNT) addition to vinyl-ester resin (VER) is a field yet to contain an in-depth repository of information. This work represents the first study on the development and characterisation of HNT-reinforced VER nanocomposites, and presents findings on their water absorption, mechanical, and thermal properties. VER composites reinforced with HNTs (1, 3, and 5 wt%) were fabricated using high speed mechanical stirring. Weight gain and FTIR spectrum analysis indicated that the addition of 5 wt% HNTs gave perceptible reduction in the water absorption behavior of the samples. Results showed that elastic modulus increased with increasing HNT content. Strength and toughness were also found to steadily increase with increasing HNT content. Favorable strength can be attributable to the large aspect ratio of HNTs, favorable adhesion and dispersion, and the suitable extent of inter-tubular interaction while enhancements to toughness can be attributable to crack bridging, deflection, and plastic deformation mechanisms. Thermal stability of nanocomposites was found remarkably enhanced by the incorporation of HNTs. The thermal stability enhancement and decrease in flammability are attributable to HNT’s barriers for heat and mass transport, presence of iron, and hollow tubular structure.